College radio as coaching professional. Analysis of the relationship between the degrees and Spanish university radio - Pinto Zúñiga, Regina; Martín-Pena, Daniel; Vivas Moreno, Agustín (Revista General de Información y Documentación, 2016)
College radio is subject to constant transformation. The rise of information and communications technologies has allowed its development and modernization as well as the proliferation of new professional profiles. This research aims to analyze the connection of the Spanish university stations with the relevant qualifications. To do this, we use a comparative methodology based on examination of descriptors and specific principal subjects of degrees such as Audiovisual Communication and Journalism, although we will be using other degrees that are acquiring more responsibilities in a radio station, such as the degree in Information and Documentation. In conclusion, structural weaknesses in the university environment are observed, but future possibilities are detected as well: A college radio station is a place of convergence between the training of students from different degrees and reality itself, a versatile medium that provides the relevance of being the first professional contact of college students with the labor market.
Keywords: Audiovisual communication; college radio; information and documentation; journalism; study plans; university degrees